1994
DOI: 10.1136/jmg.31.10.749
|View full text |Cite
|
Sign up to set email alerts
|

Mosaic uniparental disomy in Beckwith-Wiedemann syndrome.

Abstract: 1/23, p

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0
2

Year Published

1997
1997
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(54 citation statements)
references
References 30 publications
1
51
0
2
Order By: Relevance
“…This discordance can be the result of functional differences between human and mouse, be due to differences in genetic background, or reflect the fact that this group of patients with BWS has mutations in other critical genes involved in BWS. Finally, highly variable phenotypes have been associated with BWS, and, with the exception of correlations between somatic isodisomy and hemihypertrophy and between exomphalos and CDKINC mutation (47,48), no obvious correlation between phenotype and genotype has been established. It has been suggested that at least some tissues are highly sensitive to ratios of IGF-II and p57 KIP2 (40).…”
Section: Discussionmentioning
confidence: 99%
“…This discordance can be the result of functional differences between human and mouse, be due to differences in genetic background, or reflect the fact that this group of patients with BWS has mutations in other critical genes involved in BWS. Finally, highly variable phenotypes have been associated with BWS, and, with the exception of correlations between somatic isodisomy and hemihypertrophy and between exomphalos and CDKINC mutation (47,48), no obvious correlation between phenotype and genotype has been established. It has been suggested that at least some tissues are highly sensitive to ratios of IGF-II and p57 KIP2 (40).…”
Section: Discussionmentioning
confidence: 99%
“…24 The extent of pUPD at chromosome 11p has been studied by means of STR markers; the critical region for pUPD is telomeric to chromosome 11p13 and always includes the region where map some BWS genes (IGF2, H19 and CDKN1C). 19,21,23 Some cases with mosaic pUPD for the whole chromosome 11 have been also described and the clinical findings did not differ from patients with pUPD restricted to a small part of 11p. 23,25 Although the extent of segmental disomy and proportion of cells with pUPD is variable, in all BWS cases the paternal UPD is isodisomic.…”
Section: Beckwith-wiedemann Syndrome (Bws (Mim 130650)mentioning
confidence: 99%
“…26 Clinically, a clear association between mosaic UPD and hemihyperplasia exists. 15,19,22,27 In addition, it was noted that neoplasias and Wilms' tumours are more frequent in BWS patients with pUPD or H19DMR hypermethylation than in BWS patients with other molecular defect. [27][28][29] Moreover, it has been hypothesized that extremely high levels of UPD might drive severe phenotypic expression of BWS; 30 but it is often difficult to determine if levels of UPD correlate with severity of the phenotype especially when the tissues/organs involved are not usually directly tested.…”
Section: Beckwith-wiedemann Syndrome (Bws (Mim 130650)mentioning
confidence: 99%
See 2 more Smart Citations